Designing an engineering construction standards system for energy and environment sustainability: based on model-based systems engineering - Han, Song; Wang, Xiaoyu (Frontiers in Environmental Science, 2025)
With the world facing increasingly severe environmental and energy challenges, the role of the construction industry in achieving the dual-carbon goals has become increasingly prominent. However, China’s existing text-based engineering construction standards system is insufficient in effectively supporting the realization of these goals. Therefore, based on the Model-Based Systems Engineering (MBSE) approach and utilizing the Systems Modeling Language (SysML), this paper proposes a new engineering construction standards system tailored to Chinese characteristics, addressing aspects including requirements, behavior, and structure. This system not only supports the construction standard requirements in the energy transition process but also aims to improve energy efficiency, emission reduction, and resource recycling in the building industry from both energy and environmental economics perspectives. The system is validated through carbon dioxide capture standards, and the results demonstrate that the MBSE-based engineering construction standards system holds significant application prospects in promoting energy economic sustainability and environmental protection. It can provide strong support for achieving green and dual-carbon goals.